Microsatellite markers for Cattleya walkeriana Gardner, an endangered tropical orchid species. Issue 1 (14th January 2016) - Tambarussi, Evandro Vagner; Menezes, Lou C.; Ibañes, Bruna; Orth Ritter Antiqueira, Lia Maris; Dequigiovanni, Gabriel; Moreno, Maria Andréia; Ferraz, Elza Martins; Zucchi, Maria Imaculada; Veasey, Elizabeth Ann; Vencovsky, Roland
Abstract : Cattleya walkeriana, one of the most improved Brazilian Cattleyas, is a popular tropical orchid endemic from Brazil and currently endangered. In the present study, for the first time microsatellite markers were developed for C. walkeriana and their transferability was tested for the species C. loddigesii and C. nobilior . The markers were used for genotyping 26 C. walkeriana specimens from different growers and from different levels of improvement. The transferability was successful, with five polymorphic loci transferred to C. loddigesii and six polymorphic loci to C. nobilior . Eight loci were polymorphic, revealing a maximum of two to ten alleles per locus in C. walkeriana and two to four and two to five in C. loddigesii and C. nobilior, respectively. There was no significant linkage disequilibrium in the studied loci. For C. walkeriana, the observed and expected heterozygosities ranged from 0 to 0.963 and from 0.138 to 0.841, respectively. These markers identified polymorphisms and may be used to study the genetic diversity, gene flow or hybridization of these species.